Nrf2-induced miR-23a-27a-24-2 cluster modulates damage repair of intestinal mucosa by targeting the Bach1/HO-1 axis in inflammatory bowel diseases - Dun Su; Wang, Xingwen; Ma, Yan; Hao, Jinghua; Jinshen Wang; Yongqu Lu; Yulin Liu; Xingfang Wang; Zhang, Li (Free radical biology & medicine, 2021)
IBD is an idiopathic, chronic autoimmune disease associated with intense oxidative stress. As a master modulator of oxidative stress, Nrf2 has an important anti-inflammatory role in colitis by activating HO-1 transcription. Meanwhile, HO-1 expression is transcriptionally suppressed by Bach1. The Nrf2-activated HO-1 transcription depends on the inactivation of Bach1. However, how Bach1 is inactivated and how Nrf2, Bach1 and HO-1 participate in IBD remains elusive. We found that in response to inflammatory stimuli, Nrf2-induced transcription of miR-23a-27a-24-2 cluster directly inhibits Bach1 expression by binding to the 3′UTR and thereby relieved the Bach1-mediated suppression of HO-1. Besides, elevated miR-23a, miR-27a and miR-24-2 promotes the proliferation and wound healing through regulating Bach1/HO-1 expression in SW480 cell. Additionally, miR-23a, miR-27a and miR-24-2 exert a protective effect on the intestinal mucosa in DSS-induced colitis mouse model. In conclusion, our study revealed that the Nrf2/miR-23a-27a-24-2/Bach1/HO-1 regulatory axis promotes the damage repair of intestinal mucosa during the development of inflammatory bowel diseases. [Display omitted] •The expression of Nrf2, Bach1 and HO-1 in the inflammatory tissues of IBD colitis.•Nrf2 promotes the transcription of miR-23a-27a-24-2 cluster by targeting the promoter.•miR-23a-27a-24-2 cluster inhibits Bach1 protein by binding to the 3′UTR.•The cluster of miR-23a-27a-24-2 promotes the proliferation and wound healing in LPS-induced SW480 in vitro.•The cluster of miR-23a-27a-24-2 conduces to the intestinal damage repair in vivo.